Analisa Karakteristik Single Board Computer sebagai Streaming Video Server - Muhammad Adlan Hawari; Bambang Nurcahyo Prastowo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
Development in image processing is just not focused on the camera sensor and the software. Furthermore, the supporting tools has to be concerned. IP-based cameras are used widely today. Unfortunately, IP Camera has its own limitation. We cannot modificate the system as we want. This paper has introduced a system which has the same function of IP Camera but also can be modificate as we like. The system consists of Odroid XU4 and webcam as a streaming video server. Also, the test result is included in Local network which connected to 31 clients. The result shows that the video has 21,46 fps average on each client. The packet loss is only 1,20%. This means the system works properly and categorized as “very good”.